Dominant Influencing Factors of Groundwater Recharge Spatial Patterns in Ergene River Catchment, Turkey - Rukundo, Emmanuel; Dogan, Ahmet (MDPI, 2019)
Groundwater is of great significance in sustaining life on planet earth. The reliable estimation of groundwater recharge is the key understanding the groundwater reservoir and forecasting its potential accessibility. The main objective of this study was to assess the groundwater recharge and its controlling factors at the Ergene river catchment. A grid-based water balance model was adopted to determine the spatially distributed long-term groundwater recharge and other water budget components, relying upon the hydro-climatic variables, land-use, soil, geology, and relief of the investigated area. The model calculations were performed for the hydrological reference horizon of 20 years at a spatial resolution of 100 x 100 m. The base flow index (BFI) separation concept was applied to split up the simulated total runoff into groundwater recharge and direct runoff. Subsequently, the statistical methods of Pearson product-moment correlation and principal component analysis (PCA) were combined for identifying the dominant catchment and meteorological factors influencing the recharge. The average groundwater recharge over the investigated area amounts to 95 mm/year. The model validation and statistical analysis indicate that the difference between simulated and observed total runoff and recharge values is generally under 20% and no significant inconsistency was observed. PCA indicated that recharge is controlled, in order of significance, by land-use, soil, and climate variables. The findings of this research highlight the key role of spatial variables in recharge determination. In addition, the generated outputs may contribute to groundwater resource management in the Ergene river catchment.
Keywords: mGROWA; water budget components; runoff-separation; base flow; principal component analysis; WATER-BALANCE; LAND-USE; MODEL; CLIMATE; SCALE; BASIN; EVAPOTRANSPIRATION; HYDROLOGY; BASEFLOW; REGIONS; Environmental Sciences & Ecology; Water Resources